Quick training for war a few practical suggestions - Baden-Powell, Robert (Conway, 2011)
In this fascinating little book, Baden-Powell uses his extensive military experience and memories of service in Africa to distill soldiering down to 'the four C-s': Courage, Common sense, Cunning and Cheerfulness.